The dimensions of customer preference in the foodservice industry - Abdullah, Firdaus; Abdurahman, Abang Zainoren bin Abang; Hamali, Jamil (Business: Theory and Practice, 2013)
Today’s foodservice industry management must place a high priority on understanding the growing markets resulting from rapid urbanization and rising numbers of tourists. This industry has a huge impact on the global economy but it is affected by customers’ ever-changing preferences. Managers need to gain and sustain strategic advantage in this highly competitive industry, thus a local customer preference assessment is crucial. This paper presents the dimensions of customer preference in the food service industry, tested empirically for unidimensionality, reliability and validity using both exploratory and confirmatory factor analysis. A 30-item questionnaire was designed and distributed to 1000 foodservice customers, yielding a response rate of 64.2%. Factorial analysis confirmed five dimensions of customer preference, and using multiple regression, their order of importance are Halal (permissible in Islam), Price, Quality of Service, Branding and Tangibles. Knowing these dimensions relative influence may result in better allocation of resources for effective service delivery.